Penerapan Model Skrip Kooperatif Dalam Pembelajaran Materi Ketentuan Waris Dalam Islam - Basari, Basari (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2019)
Based on the results of preliminary observations of learning Islamic Religious Education in Class XII TGB 3 SMK Negeri 1 Jamblang, it shows that there are several obstacles in the implementation of teaching and learning activities, namely: less varied learning methods so that students feel bored and bored to learn Islamic Religious Education and learning outcomes are not optimal. This study aims to increase the motivation to learn Islamic Religious Education, in order to be better (maximally), both individually and classically. To achieve this goal, a classroom action research was carried out in Class XII TGB 3 SMK Negeri 1 Jamblang Cirebon Regency in learning PAI on the material